2020
DOI: 10.48550/arxiv.2008.05372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The GALAH Survey: Using Galactic Archaeology to Refine our Knowledge of TESS Target Stars

Jake T. Clark,
Mathieu Clerte,
Natalie R. Hinkel
et al.

Abstract: An unprecedented number of exoplanets are being discovered by the Transiting Exoplanet Survey Satellite (TESS ). Determining the orbital parameters of these exoplanets, and especially their mass and radius, will depend heavily upon the measured physical characteristics of their host stars. We have cross-matched spectroscopic, photometric, and astrometric data from GALAH Data Release 2, the TESS Input Catalog and Gaia Data Release 2, to create a curated, self-consistent catalog of physical and chemical properti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 113 publications
(179 reference statements)
1
5
0
Order By: Relevance
“…There is an overall good agreement between the catalogs, with a mean difference between Teff values from GALAH and TIC of −11 +121 −127 K, and Gaia of 32 +281 −163 K, with an RMS difference of 10 and 21 K, respectively. Just as Hardegree-Ullman et al ( 2020) and Clark et al (2020) showed in their work, we also find a horizontal structure within our Gaia T eff comparison near 5000 K. This further suggests that Gaia T eff values preferentially converge onto some T eff values over others. For our comparison of TIC T eff values, we only compare GALAH's values to those found with the TIC that have been derived photometrically and not spectroscopically.…”
Section: Stellar T Effsupporting
confidence: 89%
See 4 more Smart Citations
“…There is an overall good agreement between the catalogs, with a mean difference between Teff values from GALAH and TIC of −11 +121 −127 K, and Gaia of 32 +281 −163 K, with an RMS difference of 10 and 21 K, respectively. Just as Hardegree-Ullman et al ( 2020) and Clark et al (2020) showed in their work, we also find a horizontal structure within our Gaia T eff comparison near 5000 K. This further suggests that Gaia T eff values preferentially converge onto some T eff values over others. For our comparison of TIC T eff values, we only compare GALAH's values to those found with the TIC that have been derived photometrically and not spectroscopically.…”
Section: Stellar T Effsupporting
confidence: 89%
“…There are twelve CTOIs that have radii comparable to substellar and stellar objects, being larger than our 2R P limit. Of these Clark et al (2020) also found the planetary radii values for CTOI 201256771.01, CTOI 201256771.02 and CTOI 300903537.01 to be too large for a planetary object. The two candidates orbiting TIC 141622065 both have radii of 344.62±6.50R ⊕ and 339.57±6.40R ⊕ , with an orbital period separation of 0.05 days.…”
Section: Identifying False Positivesmentioning
confidence: 99%
See 3 more Smart Citations